1999
DOI: 10.1080/096382899297459
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcome of arm function after stroke: results of a follow-up study

Abstract: This is the first study to investigate the recovery of arm function after stroke over a period of 4 years. It is encouraging to note that even after 16 weeks improvement still occurred in some patients. However, considerable long-term loss of arm function, associated disability and perceived problems were found. There is an obvious need to develop effective treatment methods for hemiplegic arm function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
376
2
14

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 599 publications
(399 citation statements)
references
References 14 publications
7
376
2
14
Order By: Relevance
“…If the cutoff value of shoulder pain is NRS≥5 points, it means that the pain is severe, and 20% of stroke patients suffer severe pain (NRS≥5 points) in the early stage of stroke 12) . In addition, a study of 54 stroke patients showed the same result 15) . Accordingly, the upper extremity function of the combination of shoulder external rotation and abduction can be utilized as an index of pain caused by everyday living activities and satisfaction with life.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…If the cutoff value of shoulder pain is NRS≥5 points, it means that the pain is severe, and 20% of stroke patients suffer severe pain (NRS≥5 points) in the early stage of stroke 12) . In addition, a study of 54 stroke patients showed the same result 15) . Accordingly, the upper extremity function of the combination of shoulder external rotation and abduction can be utilized as an index of pain caused by everyday living activities and satisfaction with life.…”
Section: Discussionsupporting
confidence: 60%
“…It is reported to have high validity and sensitivity in the evaluation of the severity of pain of the elderly and stroke patients 20) . When functional movement of the upper extremities is performed in the HBN test, if shoulder pain is assessed as NRS≥5 points, it means that patients feel the pain with the inverse value of the probability of which the pain appears 12,15) . In the HBN test, it was reported that for a NRS≥5 in the determination of pain in a stable condition, the ROC curve is 0.845, Sensitivity is 96.7 and Specificity is 72.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agreement between the measurements of the logit values (i.e., parametric data) was evaluated by the intra-class correlation coefficient (ICC). Different subforms of ICCs are available for different study designs and the most commonly used are ICC 1,1 , ICC 2,1 and ICC 3,1 . In practice, their values are often very similar.…”
Section: Methodsmentioning
confidence: 99%
“…52 Psychometric properties: the ARA has good intrarater, interrater and test ± retest reliability in stroke patients (all Spearman correlations 40.98). 52,53 The concurrent validity of the ARA has been con®rmed by comparison with the Brunnstrom-Fugl-Meyer Assessment (r40.91), 54,55 with the Sollerman test (r=0.94), 52 and with the motor assessment scale (MAS) (ICC=0.98). 56 Normative…”
Section: Name: the Physical Capacities Evaluation Of Hand Skill (Pce)mentioning
confidence: 99%